Comparison of aquatic macroinvertebrate communities of Lake Ahémé (Benin, West Africa) across the short and long wet seasons - ODOUNTAN, Hamed Olaniran; SIDI, Nadjib; de BISTHOVEN, Luc Janssens; Bird, Matthew S.; ABOU, YOUSSOUF (My University, 2022)
Seldom investigated for its biodiversity, the biomonitoring of Lake Ahémé is expected to increase in future and a prerequisite is the design of an appropriate sampling strategy. Here, we assessed macroinvertebrate assemblages in relation to environmental conditions in Lake Ahémé during the short and long wet seasons (SWS and LWS, respectively). This will help optimise sampling strategies for the future, when sampling only during the SWS or the LWS. A total of 4049 macroinvertebrates from 28 families and 32 genera were collected. Abundance was significantly higher at sites sampled during the SWS. Molluscs were the most dominant taxon and accounted for 92.8% of individuals collected during this study. This was followed by annelids, insects and crustaceans representing 3.7%, 3.2% and 0.3% of the total abundance, respectively. Biodiversity indices showed a significantly higher diversity in the SWS and higher spatial variation in the macroinvertebrate community. The first three axes of the non-metric multidimensional scaling revealed spatial changes in the macroinvertebrate community during the SWS and LWS. These changes were driven by salinity, conductivity, pH, temperature, dissolved oxygen and water depth. No taxa could be assigned as indicators in the LWS whereas diverse brackish and freshwater species characterised the SWS. As a result, when considering sampling during the wet seasons, SWS sampling should suffice for a qualitative study whereas an accurate ecological investigation requires both SWS and LWS.
Keywords: aquatic ecology benthic invertebrates biomonitoring coastal lagoons seasonal differentiation